Seruit and the Construction of Lampungese in Digitalized Multicultural Urban Setting - Nurdin, Bartoven Vivit; Abdulgani, Fuad; Wibisono, Damar; Ariyanto, Komang (Universitas Negeri Surabaya, 2024)
This paper examines how a particular cultural product (cuisine) from a demographically minority ethnic group is transformed in a multicultural social setting. The expanding process of commodification and the development of the urban culinary industry, supported by innovations in digital technology and media, provide opportunities for ethnic cuisines to compete with other culinary traditions. This research aims to determine how the cultural identity embedded in specific cuisines is built in the culinary market and how the intrinsic value of ethnic culinary traditions is transformed in multiethnic societies. The theory used is food culture and food habits. (Foster and Anderson 1978; Jerome, Kandel, and Pelto 1980). This study used qualitative research methods with an ethnographic approach. Data was collected through interviews, observations, and the author's participant observation as a citizen of the city under study. The study found that togetherness is an intrinsic value of Lampung's seruit commensality that is adaptive amidst socio-cultural transformation into a multicultural society. Seruit becomes an arena for constructing Lampungnese during a multiethnic urban society and growing commercial economy. Sharing meals (seruit commensality) can promote harmony among Lampung's urban ethnic groups. Mass and digital media have transformed Lampung's identity